Epidemiology and health consequences of early marriage: focus on Delta State Nigeria - Agege, Emmanuel A.; Nwose, Ezekiel Uba; Nwajei, Samuel D.; Odoko, Joseph E.; Moyegbone, John E.; Igumbor, Eunice O. (International Journal Of Community Medicine And Public Health, 2020)
Early marriage occurs for several reasons including gender inequality, poverty, insecurity and tradition. Marrying at such a young age means that these young girls are forced into sexual relations and often get pregnant when they are not ready, causing health challenges and adding to the health burden in developing countries. This paper reviews the epidemiology of early marriage with particular regards to the public health concepts and negative consequences of early marriage. This was a narrative review of previous works on early marriage. Evaluations included the statistics of the negative consequences on women and how best the practices have been ameliorated to its barest minimum. No data available on the previous works dearth of contextualized epidemiological information about Delta State Nigeria. However, available data shows as high as 88% prevalence rate of child marriage in Nigeria, with unexpected pregnancy at 23% being the major cause, maternal mortality at 90%, VVF over 500,000–1,000,000 reported annually in developing countries as the major health consequences. The causes, consequences and prevalence of early marriage constitute reasons for public health concerns to stem the tide. Willful and urgent attention is needed to prevent the pitiable situation of the victims, especially girls. Health literacy is a primary healthcare concept of community educational outreach to adopt.